'Tied up in a legal mess': The alcohol industry's use of litigation to oppose minimum alcohol pricing in Scotland. Issue 1 (February 2020) - Hawkins, Benjamin; McCambridge, Jim
Abstract : This article examines the alcohol industry's legal challenges to minimum unit pricing (MUP) in Scotland through the stages heuristic of the policy process. It builds on previous studies of alcohol pricing policy in Scotland and across the UK, and of the use of legal challenges by health harming industries to oppose health policy globally. Having failed to prevent MUP passing into law, industry actors sought to frustrate the implementation of the legislation via challenges in the Scottish, European and UK courts. However, the relevance of legal challenges is not limited to the post-legislative stage of the policy process but was foreshadowed in all earlier stages of the policy process. The potential for a legal challenge to MUP, and the alcohol industry's clearly articulated intention to pursue such action, was used by industry actors to seek to prevent the adoption of MUP in the agenda setting, policy formulation and legislative stages and created significant 'regulatory chill' in other areas of Scottish and UK alcohol policy. Litigation, and the prospect of it, was thus part of a coherent and integrated long-term strategy which adapted to changes in the political climate and to different stages in the policy process. While both the rhetoric and reality of litigation failed to prevent policy implementation, it succeeded in causing a delay of six years, imposing significant costs on the Scottish government and creating policy inertia in Scottish alcohol policy subsequently. Moreover, the inclusion of a 'sunset clause' in the legislation, requiring ongoing evaluation of the policy's effects, presents additional opportunities for the industry to reverse MUP. Thus, industry strategies to undermine MUP and delay further alcohol policy developments require ongoing attention by policy actors and scholars.